NURSING INFORMATICS - Ponchitra, R. (Journal of Health and Allied Sciences NU, 2013)
Computers have opened for us a world of information. New and emerging technologies will continue to have an effect on the health care delivery system. Nurses as a major player in health care, will be part of this ever growing era technology. A nurse must know generalized applications such as word processing, as well as specialized applications such as clinical information system. Virtual reality (simulation) and ubiquitous(every where) computing are emerging and being used in education and other areas in health care nursing knowledge workers must be able to understand the evolving specialty, nursing informatics, in order to begin to harness and use the tools available for managing the vast amount of health care data and information. This article mentions in detail about Nursing Informatics and therefore highlights that nursing informatics capabilities be appreciated, promoted, expanded and advanced to facilitate the work of the Nurse, improve patient care, and enhance the Nursing profession.
Keywords: Clinical Information System; Virtual reality; Ubiquitous computing